1988
DOI: 10.1093/nar/16.23.10953
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of human minisatellites by the polymerase chain reaction: towards DNA fingerprinting of single cells

Abstract: Hypervariable minisatellites can be amplified from human DNA by the polymerase chain reaction, using primers from DNA flanking the minisatellite to amplify the entire block of tandem repeat units. Minisatellite alleles up to 5-10 kb long can be faithfully amplified. At least six minisatellite loci can be co-amplified from the same DNA sample and simultaneously detected to provide a reproducible and highly variable DNA fingerprint which can be obtained from nanogram quantities of human DNA. The polymerase chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
154
0
8

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 457 publications
(168 citation statements)
references
References 30 publications
6
154
0
8
Order By: Relevance
“…Based on the estimate of 6 pg of DNA per diploid cell, 23 we calculate that the lowest detection limit of our IgH PCR assay is 10 to 20 B cell genome equivalents. In other words, a limiting dilution down to one B cell will not be detectable by our assay, and hence will not yield a pseudomonoclonal band.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the estimate of 6 pg of DNA per diploid cell, 23 we calculate that the lowest detection limit of our IgH PCR assay is 10 to 20 B cell genome equivalents. In other words, a limiting dilution down to one B cell will not be detectable by our assay, and hence will not yield a pseudomonoclonal band.…”
Section: Discussionmentioning
confidence: 99%
“…Each result was then converted into estimates of the actual amounts of amplifiable gDNA in mg and multiplied by 3.3 Â 10 5 to estimate the number of amplifiable haploid genomes. 22,23 PCRs were performed using PrimerDesign (Southampton, UK) master mix under standard conditions, with 5 ml of gDNA (approximately 100 ng). PCRs were set up on a RotorGene CAS1200 robot and run on the RotorGene 6000 platform (Cambridge, UK).…”
Section: Absolute Quantification Of Gdna Fusions In Pre-imatinib Samplesmentioning
confidence: 99%
“…PCR amplification of five different minisatellite loci were used to analyze of MC (D1S80, 28 D11S533, 29 IGHJ, 30 33.6 31 and TCRAD 32 ) in the initial screening process before SCT, to find an informative locus separating the donor and the recipient. Data concerning the VNTR primers used in this study are shown in Table 2.…”
Section: Vntr Analysismentioning
confidence: 99%